Effects of lower limb biomechanical characteristics on jump performance in female volleyball players based on long Stretch–Shortening cycle movements - Deng, Beiwang; Li, Yueming; Lin, Gesheng; Yan, Ruixiang; He, Jianxin; Li, Duanying; Sun, Jian (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundIn volleyball, certain maneuvers (e.g., depth jumps) involve a long stretch-shortening cycle (long-SSC) characterized by a prolonged landing-to-takeoff phase (ground contact time ≥222 ms). However, the key biomechanical factors influencing jump height in such long-SSC movements remain unclear, particularly in female athletes. This study investigated depth jump biomechanics in female volleyball players to identify performance-related factors and inform training optimization.MethodsEighteen trained female volleyball players performed maximal-effort depth jumps under 3D motion capture. Pearson correlation analysis examined relationships between biomechanical variables and jump height. Participants were then divided into high (HJG) and low (LJG) jump-height groups based on a median split and compared using independent samples t-tests.ResultsJump height correlated positively with peak propulsion velocity, peak propulsion power, knee flexion-extension angle, peak ankle moment, and peak propulsion impulse (all p < 0.05). Compared with LJG, HJG exhibited significantly greater jump height, propulsion velocity, knee flexion-extension angle, and ankle moment but lower leg stiffness and braking force. Differences in contact time, propulsion impulse, and hip angle had moderate effect sizes.ConclusionPeak propulsion velocity was the strongest correlate of jump height in long-SSC depth jumps. Propulsion-phase variables, particularly ankle torque and impulse, were more influential than braking-phase variables. In contrast to short-SSC tasks, high lower-limb stiffness appears to provide limited benefit for maximizing performance in long-SSC movements. Training for female volleyball players should therefore prioritize developing propulsion-phase power and ankle strength for these types of jumps.Trial registration numberChiCTR2400094392; Registration date: 22/12/2024.